Impact of Industrialisation and Mining on Occupational Structure of Tribes in Singhbhum Region - Dr. Nigar Alam, (IJRDO - Journal of Social Science and Humanities Research, 2019)
Industrial concentrations are regarded as the poles of growth which brings regional development. It is assumed that industrialisation together with mining eradicates poverty is a myth in some states of India. The situation is almost different in states like Chhattisgarh, Madhya Pradesh and Jharkhand. Most of the mineral graved states are not as much developed as the other states not having very giant industrial clusters and mineral excavations. Further the development should all sections of population within its influence zone. It should influence tribes as well as rural masses. In this study an attempt has been made to examine the influence of industrialisation and mining on tribes. Singhbhum region of Jharkhand has been selected for this purpose. Singhbhum region of Jharkhand is one of the most significant industrial and mining region of India. The main objective behind this investigation is to know the influence of mining and industrialization on occupational structure of tribes in Singhbhum region. An attempt has been made to study the presence of tribes in various occupations such as industry, mining, food processing industries etc. This study is mainly based on primary data. Though secondary sources of information has also been used for having basic knowledge of the area. Primary data were collected from the three selected areas of Ghatsila division in East Singhbhum region of Jharkhand. The tribes dominated pockets, Jharia, Ichra and Ullidih of Ghatsila division of Singhbhum region are selected for data collection purposes.